Influência de tensoativos não iônicos na destilação molecular de petróleo - Lucena, Izabelly Larissa (2013)
The molecular distillation is show as an alternative for separation and purification of various kinds of materials. The process is a special case of evaporation at high vacuum, in the order from 0.001 to 0.0001 mmHg and therefore occurs at relatively lower temperatures, preserves the material to be purified. In Brazil, molecular distillation is very applied in the separation of petroleum fractions. However, most studies evaluated the temperature of the evaporator, condenser temperature and flow such variables of the molecular distillation oil. Then, to increase the degree of recovery of the fraction of the distillate obtained in the process of the molecular distillation was evaluated the use nonionic surfactants of the class of nonylphenol ethoxylate, molecules able to interact in the liquid-liquid and liquid-vapor interface various systems. In this context, the aim of this work was to verify the influence of commercial surfactant (Ultranex-18 an Ultranex-18-50) in the molecular distillation of a crude oil. The physicochemical characterization of the oil was realized and the petroleum shown an API gravity of 42°, a light oil. Initially, studied the molecular distillation without surfactant using star design experimental (2H ± ) evaluated two variables (evaporator temperature and condenser temperature) and answer variable was the percentage in distillate obtained in the process (D%). The best experimental condition to molecular distillation oil (38% distillate) was obtained at evaporator and condenser temperatures of 120 °C and 10 ° C, respectively. Subsequently, to determine the range of surfactant concentration to be applied in the process, was determined the critical micellar concentration by the technique of scattering X-ray small angle (SAXS). The surfactants Ultranex-18 an Ultranex-18-50 shown the critical micelle concentration in the range of 10-2 mol/L in the hydrocarbons studied. Then, was applied in the study of distillation a concentration range from 0.01 to 0.15 mol/L of the surfactants (Ultranex- 18 and 50). The use of the nonionic surfactant increased the percentage of hydrocarbons in the range from 5 to 9 carbons in comparison to the process carried out without surfactant, and in some experimental conditions the fraction of light compounds in the distilled was over 700% compared to the conventional process. The study showed that increasing the degree of ethoxylation of Ultranex18 to Ultranex-50, the compounds in the range of C5 to C9 reduced the percentage in the distilled, since the increase of the hydrophilic part of the surfactant reduces its solubility in the oil. Finally, was obtained an increase in the degree of recovery of light hydrocarbons, comparing processes with and without surfactant, obtained an increase of 10% and 4% with Ultranex-18 and Ultranex-50, respectively. Thus, it is concluded that the Ultranex- 18 surfactant showed a higher capacity to distillation compared with Ultranex-50 and the application of surfactant on the molecular distillation from petroleum allowed for a greater recovery of light compounds in distillate